2005
DOI: 10.1038/sj.onc.1209206
|View full text |Cite
|
Sign up to set email alerts
|

Physical interaction of apoptosis-inducing factor with DNA and RNA

Abstract: Apoptosis-inducing factor (AIF) is a mitochondrial flavoprotein, which upon apoptosis induction translocates to the nucleus where it interacts with DNA by virtue of positive charges clustered on the AIF surface. Here we show that the AIF interactome, as determined by mass spectroscopy, contains a large panel of ribonucleoproteins, which apparently bind to AIF through the RNA moiety. However, AIF is devoid of any detectable RNAse activity both in vitro and in vivo. Recombinant AIF can directly bind to DNA as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 50 publications
4
40
2
Order By: Relevance
“…[49][50][51] Our biochemical apoptosis results in the translocation of AIFM1 to the nucleus, where it binds DNA and affects chromosome condensation and fragmentation, although the precise mechanism of AIFM1 nuclear function is unknown. 48,[52][53][54][55] We showed that AIFM1 knockdown in striatal cells attenuated toxicity of expanded Htt-N585-82Q fragment (Fig. 3D).…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51] Our biochemical apoptosis results in the translocation of AIFM1 to the nucleus, where it binds DNA and affects chromosome condensation and fragmentation, although the precise mechanism of AIFM1 nuclear function is unknown. 48,[52][53][54][55] We showed that AIFM1 knockdown in striatal cells attenuated toxicity of expanded Htt-N585-82Q fragment (Fig. 3D).…”
Section: Discussionmentioning
confidence: 99%
“…Upon apoptosis induction, AIF translocates to the nucleus where it contributes to chromatin condensation via a direct interaction with DNA (Ye et al, 2002;Vahsen et al, 2006) and recruits other proteins into the 'degradosome', which mediates chromatinolysis Cande et al, 2004a). Microinjection of recombinant AIF is sufficient to induce hallmarks of apoptosis (chromatin condensation, rounding up of cells, phosphatidyl serine exposure) .…”
Section: Chemotherapy and Mitochondriamentioning
confidence: 99%
“…the inhibitor of apoptosis proteins (IAPs). AIF and EndoG translocate to the nucleus where they mediate chromatin condensation and large-scale DNA fragmentation, independently from caspases [16,17,19,20].…”
Section: Intrinsic and Extrinsic Apoptosis Pathwaysmentioning
confidence: 99%